Translation acts, or how to do things with translations - Esteves, Lenita (2017)
This paper analyses the act of translation in the light of the Theory of Speech Acts as proposed by John Langshaw Austin in How to do things with words, arguing that the way Austin develops his theory, in a non-linear fashion, is adequate for a theorization of translation acts. The paper also proposes that translation acts should be considered as “emic” entities, that is, irreducibly cultural entities. This proposal is in turn inspired by Kanavillil Rajagopalan’s statement about illocutionary acts: For this author, illocutionary acts are “inextricably cultural unities of analysis, which can only be understood as institutional facts specifi c to each speech community (1992a: 120).